PM10 emission efficiency for agricultural soils: Comparing a wind tunnel, a dust generator, and the open-air plot - Avecilla, Fernando (2018)
The PM10 emission efficiency of soils has been determined through different methods. Although these methods imply important physical differences, their outputs have never been compared. In the present study the PM10 emission efficiency was determined for soils through a wide range of textures, using three typical methodologies: a rotary-chamber dust generator (EDG), a laboratory wind tunnel on a prepared soil bed, and field measurements on an experimental plot. Statistically significant linear correlation was found (p < 0.05) between the PM10 emission efficiency obtained from the EDG and wind tunnel experiments. A significant linear correlation (p < 0.05) was also found between the PM10 emission efficiency determined both with the wind tunnel and the EDG, and a soil texture index (%sand+%silt)/(%clay+%organic matter) that reflects the effect of texture on the cohesion of the aggregates. Soils with higher sand content showed proportionally less emission efficiency than fine-textured, aggregated soils. This indicated that both methodologies were able to detect similar trends regarding the correlation between the soil texture and the PM10 emission. The trends attributed to soil texture were also verified for two contrasting soils under field conditions. However, differing conditions during the laboratory-scale and the field-scale experiments produced significant differences in the magnitude of the emission efficiency values. The causes of these differences are discussed within the paper. Despite these differences, the results suggest that standardized laboratory and wind tunnel procedures are promissory methods, which could be calibrated in the future to obtain results comparable to field values, essentially through adjusting the simulation time. However, more studies are needed to extrapolate correctly these values to field-scale conditions.